2022
DOI: 10.1155/2022/6458350
|View full text |Cite
|
Sign up to set email alerts
|

Progressive Distributed and Parallel Similarity Retrieval of Large CT Image Sequences in Mobile Telemedicine Networks

Abstract: Computed tomography image (CTI) sequence is essentially a time-series data that typically consists of a large amount of nearby and similar CTIs. Due to the high communication and computational costs, it is difficult to perform a progressive distributed similarity retrieval of the large CTI sequence (CTIS)s, particularly in resource-constraint mobile telemedicine network (MTN)s. In this paper, we present a Dprs method—progressive distributed and parallel similarity retrieval scheme for the CTISs in the MTN. To … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(35 citation statements)
references
References 29 publications
0
18
0
Order By: Relevance
“…The study also identified some critical factors that influence the thermal behavior of solid propellants, such as the presence of additives and the effects of moisture 48,49 . The study results showed that silencing GTF2B expression led to a significant decrease in the proliferation of A549 cells, suggesting that GTF2B plays a role in promoting cell growth 50,51 .…”
Section: Related Workmentioning
confidence: 89%
“…The study also identified some critical factors that influence the thermal behavior of solid propellants, such as the presence of additives and the effects of moisture 48,49 . The study results showed that silencing GTF2B expression led to a significant decrease in the proliferation of A549 cells, suggesting that GTF2B plays a role in promoting cell growth 50,51 .…”
Section: Related Workmentioning
confidence: 89%
“…Considering the lack of valid data, the following image augmentation technique is used to increase the number of CT scans [42]. Some common types of image augmentation that are applied to COVID-19 CT scans include [43]:…”
Section: Sirm Datasetmentioning
confidence: 99%
“…However, exploring such questions relies on vast amounts of relevant data. A large subject of research is medical information systems, which aid clinicians in providing quicker and more accurate medical diagnoses ( Li C. et al, 2022 ; Liu S. et al, 2022 ; Zhuang et al, 2022 ). In this regard, manual analysis is impractical because it is time-consuming, inefficient, and error-prone for vast amounts of data.…”
Section: Introductionmentioning
confidence: 99%